Objects and subjects of registration and permit-licensing procedures in the activities of the National Police - О. А. Bud (Bulletin of Kharkiv National University of Internal Affairs)
The study of objects and subjects of registration and permit-licensing procedures in the activities of the National Police has determined the need to delimit the categories of objects and subjects with the categories “subjects” and “participants” of the procedures that are similar in meaning. As a result, taking into account the specifics of the content and essence of both of the specified types of procedures, a number of conclusions have been drawn.